Comparing the vaginal wall sling with autologous rectus fascia and polypropylene sling: Short term outcomes and patient satisfaction. (December 2018) - Wagner, Hillary; Cheng, Julie W.; Austin Krishingner, G.; Kim, Kevin; Chung, Kristin M.; Kelly, Isaac; Staack, Andrea
Abstract: Objectives: Many women are affected by stress urinary incontinence (SUI). Due to investigations of the safety of synthetic mesh slings, there has been renewed interest in autologous slings. The aim of this study is to evaluate whether different sling material affects outcomes and patient satisfaction. Methods: A retrospective review was performed of patients who underwent sling placement between May 2011 and April 2017 for SUI or stress-predominant mixed urinary incontinence. Patients were divided based on the sling material used: vaginal wall sling (VWS), rectus fascia sling (RFS), and soft polypropylene sling (SPS). Outcomes were compared using a Likert scale, the validated SEAPI score system, Incontinence Impact Questionnaire 7 (IIQ-7), and Incontinence Symptom Severity Index (ISSI). Results: There were 228 patients that underwent sling placement with 94 receiving VWS, 62 RFS, and 72 SPS. Mean follow-up was 14 months. There was no statistical difference in postoperative pad usage or satisfaction score between the groups. All three groups had a statistically significant postoperative improvement in subjective SEAPI scores and daily pad use. The VWS and RFS groups had significant improvement in their ISSI. The VWS group also had postoperative improvement in IIQ-7 score. Complication rates were rare and similar between all three groups. Conclusions: Patient satisfaction and outcomes were overall similar between all three sling materials. Based on our outcomes, we continue to use the VWS as a treatment option for patients with SUI and redundant vaginal wall tissue that are opposed to synthetic mesh slings.